Realization of ultra‐high‐efficient fluorescent blue OLED. Issue 5 (27th April 2022) - Tasaki, Satomi; Nishimura, Kazuki; Toyoshima, Hiroaki; Masuda, Tetsuya; Nakamura, Masato; Nakano, Yuki; Itoi, Hiroaki; Kambe, Emiko; Kawamura, Yuichiro; Kuma, Hitoshi
Abstract: The bilayer structure for an emitting layer (EML) was developed to improve performances of a fluorescence blue organic light emitting diode. By functionally separating the EML into the charge recombination and the triplet–triplet fusion (TTF) zone, we successfully suppressed the quenching of triplet excitons by excess carriers to make more TTF efficient and the local degradation within the EML to make the lifetime longer. In the bottom emission device with the bilayer EML, 12% of external quantum efficiency (EQE) and 450 h of LT95 were achieved. Furthermore, we achieved over 14% of EQE by optimizing the material combinations. Abstract : A bilayer emitting layer was developed with functionally separating the emitting layer into the recombination and triplet–triplet fusion zone. In the bottom emission device, we successfully achieved over 14% of EQE.